2016
DOI: 10.1016/j.ecosys.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Gender equality in Muslim-majority countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 39 publications
3
15
0
1
Order By: Relevance
“…283-285). Discrimination against women (Cooray and Potrafke, 2011;Gouda and Potrafke 2016) and homosexuals (Berggren et al, 2017) has also been shown to be prevalent in Muslim societies. Berggren et al (2018) document that these negative attitudes persist even among second-generation immigrants from Muslim countries, although they were born and raised in Western societies.…”
Section: Many Argue That the Persecution And Discrimination Faced By mentioning
confidence: 99%
“…283-285). Discrimination against women (Cooray and Potrafke, 2011;Gouda and Potrafke 2016) and homosexuals (Berggren et al, 2017) has also been shown to be prevalent in Muslim societies. Berggren et al (2018) document that these negative attitudes persist even among second-generation immigrants from Muslim countries, although they were born and raised in Western societies.…”
Section: Many Argue That the Persecution And Discrimination Faced By mentioning
confidence: 99%
“…This hypothesis is given empirical support in and. Somewhat relatedly, Voigt (2015, 2018) andGouda and Potrafke (2016) find indications that legislation in states where Islam has a strong position tends to discriminate women and protect minorities worse. Moreover,Berggren and Bjørnskov (2011) find a negative relation between religiosity and social trust.…”
mentioning
confidence: 99%
“…In addition to describing the culturally adapted CBT techniques, the authors highlight the issues of gender discrimination and female sexuality in Muslim countries (Gouda and Potrafke, 2016). Culture, religion and spirituality influence the belief systems of people, including beliefs about illness, its causes and treatment (Cinnirella and Loewenthal, 1999;Ismail et al, 2005;Razali et al, 1996).…”
Section: Summary and Discussionmentioning
confidence: 99%